Health Care Spending in the New EU Member States : Controlling Costs and Improving Quality - Chawla, Mukesh (Washington, DC: World Bank, 2012)
The main objectives of this study, Health care spending in the new EU member states: controlling costs and improving quality, are to take stock of recent trends in health expenditure aggregates in the public sector and to identify specific areas of reform consistent with the objectives of consolidating the fiscal situation in these countries without adversely affecting the production, delivery and utilization of health services. The book begins with an introduction and the rest of this study is organized as follows: Chapter 2 discusses trends and structure of health expenditures in the EU8. Chapter 3 assesses the nature and extent of indebtedness in the health sectors. Chapter 4 discusses the key expenditure areas. Chapter 5 presents population ageing and proliferation of medical technology as the future spending pressure points in the health sector. Chapter 6 focuses on the management of health expenditures. Finally, Chapter 7 concludes.